"Other" White Storytellers: Emancipating Albinism Identity through Personal Narratives. Issue 2 (15th March 2019) - Miller, Niya Pickett
Abstract: Through the rhetoric of whiteness, the term "albino" distinguishes an albinic body from the "normal" white skin color of a White person. However, "albino" bodies may reposition themselves closer towards perceived normalcy via emancipatory rhetoric. This study analyzes the emancipatory rhetoric within TEDx talks presented by albinic, Black fashion models, Diandra Forrest and Shaun Ross.It is argued that the two utilize personal narratives to un-otherize(emancipate) from the stereotypical "albino" identity and highlight the complexity of race and difference-making in our culture.